Association of Dipeptidiyl Peptidase-4 Inhibitors and Bullose Pemphigoid: A Report of Four Cases - Neslihan USLU; Kagan GUNGOR; Gonca TAMER; Bulent CAN (Medeniyet Medical Journal)
Dipeptidyl-peptidase 4 inhibitors (DPP4i) are commonly used as antidiabetic medications. Although these drugs are generally recognized for their favorable clinical safety profile, emerging evidence points to the potential for adverse events associated with DPP4i. Notably, cases of bullous pemphigoid (BP) linked to DPP4i therapy have recently been documented in the medical literature. This report presents four cases of BP in elderly patients resulting from DPP4i treatment, involving two cases with ligandliptin and two with vildagliptin use. Successful remission was achieved in all cases through discontinuation of the implicated medication and implementation of topical corticosteroid therapy. It is imperative for clinicians to be vigilant about the potential risk of BP development when employing DPP4i drugs, particularly in the context of elderly patients with diabetes.